On Properties of UBAC Class of Life Distributions - Abu-Youssef, Shaaban Ebrahim (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
Some properties of the used better than aged in convex ordering( UBAC) class of life distributions are given. These properties include moment inequalities and moment generating functions behavior. Nonparametric estimation of UBAC survival function are discussed. In addition testing of the survival function of this class based on moment inequalities are introduced.